INFLUENCE OF TRUST AND TRANSPARENCY ON PERFORMANCE OF PHARMACEUTICAL FIRMS IN KENYA - Kiriinya, Akwalu Ezekiel; Ngugi, Dr. P. Karanja Ngugi; Mwangangi, Dr. Patrick; Odhiambo, Prof. Romanus (European Journal of Business and Strategic Management, 2018)
.